Transport and noise properties of a normal metal–superconductor–normal metal junction with mixed singlet and chiral triplet pairings. (10th November 2016) - Paul, Ganesh C; Dutta, Paramita; Saha, Arijit
Abstract: We study transport and zero frequency shot noise properties of a normal metal–superconductor–normal metal (NSN) junction, with the superconductor having mixed singlet and chiral triplet pairings. We show that in the subgapped regime when the chiral triplet pairing amplitude dominates over that of the singlet, a resonance phenomena emerges out at zero energy where all the quantum mechanical scattering probabilities acquire a value of 0.25. At the resonance, crossed Andreev reflection mediating through such junction, acquires a zero energy peak. This reflects as a zero energy peak in the conductance as well depending on the doping concentration. We also investigate shot noise for this system and show that shot noise cross-correlation is negative in the subgapped regime when the triplet pairing dominates over the singlet one. The latter is in sharp contrast to the positive shot noise obtained when the singlet pairing is the dominating one.